Synthesis and medicinal use of Metal complexes of Schiff Bases - Chaudhary, Nrendra Kumar (BIBECHANA, 2012)
Different Schemes for the synthesis of Schiff bases have been discussed. Solvent free synthesis by microwave irradiation technique is observed to be rapid, more efficient and more economical and at the same time may play a pivotal role in the progress of Schiff base synthesis. Mechanism for the synthesis of Schiff bases at controlled pH range has been studied. Biological functions of metal complexes of Schiff bases have found to be increased potentiality in presence of transition metal ions. DOI: http://dx.doi.org/10.3126/bibechana.v9i0.7178 BIBECHANA 9 (2013) 75-80